2022
DOI: 10.1016/j.bioactmat.2021.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite electrospun fibers of poly(ε-caprolactone)/bioactive glass with shape memory properties

Abstract: Electrospun fibers of shape memory triethoxysilane-terminated poly(epsilon-caprolactone) (PCL-TES) loaded with bioactive glasses (BG) are here presented. Unloaded PCL-TES, as well as PCL/BG nanocomposite fibers, are also considered for comparison. It is proposed that hydrolysis and condensation reactions take place between triethoxysilane groups of the polymer and the silanol groups at the BG particle surface, thus generating additional crosslinking points with respect to those present in the PCL-TES system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Orthopedic implants with SME could reduce the size of the surgical incision area and hence, reduce the postoperative time and possible complications [ 97 ]. Recent studies have shown the possibility of poly(α-hydroxy ester) with bioactive fillers to enhance the biological performance and shape memory properties for internal fixation systems [ 98 , 99 , 100 , 101 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Orthopedic implants with SME could reduce the size of the surgical incision area and hence, reduce the postoperative time and possible complications [ 97 ]. Recent studies have shown the possibility of poly(α-hydroxy ester) with bioactive fillers to enhance the biological performance and shape memory properties for internal fixation systems [ 98 , 99 , 100 , 101 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In the medical field, a nanofiber-integrated negative sorting device can be used for cancer diagnosis [ 52 ]. Nanocomposites with shape-memory properties enable the fabrication of shape-programmable bone scaffolds [ 53 ]. Core–shell lipid-coated nanoparticles and nanodelivery systems of melittin can be used for cancer therapy [ 54 , 55 ].…”
Section: High-voltage Electrospinningmentioning
confidence: 99%
“…With the aim of producing materials with shape-memory behavior, sometimes polymers without this property are modified in order to achieve the desired SM properties. For example, Liverani et al [163] used PCL modified at chain-ends, producing a triethoxysilaneterminated poly(epsilon-caprolactone) (PCL-TES) loaded with bioactive glasses (BG), which are capable of binding the host tissue and generating a coating of hydroxycarbonate apatite. The SiO 2 domains subsequently formed the reaction between the ends group, constituting the permanent crosslinking point.…”
Section: Tissue Engineeringmentioning
confidence: 99%